Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.18632/oncotarget.27940
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma cells that have undergone an epithelial-mesenchymal transition differentiate into endothelial cells and contribute to tumor growth

Abstract: Hypoxia stimulates neoangiogenesis, promoting tumor outgrowth, and triggers the epithelial-mesenchymal transition (EMT), which bestows cells with mesenchymal traits and multi-lineage differentiation potential. Here, we investigated whether EMT can confer endothelial attributes upon carcinoma cells, augmenting tumor growth and vascularization. Following orthotopic implantation of MCF-7 human epithelial breast cancer cells into mice, tumors of different sizes were immunostained for markers of hypoxia and EMT. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Induction of EMT in a weakly tumorigenic MCF-7 breast cancer cel line promoted trans-differentiation of cancer cells into CD31-positive endothelial cells which facilitated vascularization and growth of tumor xenografts in mice [92]. Mechanis tically, FOXC2 was shown to be a key factor in the acquisition of endothelial phenotypic and functional characteristics in vitro and in vivo (path B in Figure 7) [92]. In addition to the well-documented paracrine effects of FOXC2 on endothelial cells, it has been shown that FOXC2-expressing cancer cells are capable of trans-differentiation into endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Induction of EMT in a weakly tumorigenic MCF-7 breast cancer cel line promoted trans-differentiation of cancer cells into CD31-positive endothelial cells which facilitated vascularization and growth of tumor xenografts in mice [92]. Mechanis tically, FOXC2 was shown to be a key factor in the acquisition of endothelial phenotypic and functional characteristics in vitro and in vivo (path B in Figure 7) [92]. In addition to the well-documented paracrine effects of FOXC2 on endothelial cells, it has been shown that FOXC2-expressing cancer cells are capable of trans-differentiation into endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the well-documented paracrine effects of FOXC2 on endothelial cells, it has been shown that FOXC2-expressing cancer cells are capable of trans-differentiation into endothelial cells. Induction of EMT in a weakly tumorigenic MCF-7 breast cancer cell line promoted trans-differentiation of cancer cells into CD31-positive endothelial cells, which facilitated vascularization and growth of tumor xenografts in mice [92]. Mechanistically, FOXC2 was shown to be a key factor in the acquisition of endothelial phenotypic and functional characteristics in vitro and in vivo (path B in Figure 7) [92].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation